Recentering neuroscience on behavior: The interface between brain and environment is a privileged level of control of neural activity. (July 2022) - Branchi, Igor
Abstract: Despite the huge and constant progress in the molecular and cellular neuroscience fields, our capability to understand brain alterations and treat mental illness is still limited. Therefore, a paradigm shift able to overcome such limitation is warranted. Behavior and the associated mental states are the interface between the central nervous system and the living environment. Since, in any system, the interface is a key regulator of system organization, behavior is proposed here as a unique and privileged level of control and orchestration of brain structure and activity. This view has relevant scientific and clinical implications. First, the study of behavior represents a singular starting point for the investigation of neural activity in an integrated and comprehensive fashion. Second, behavioral changes, accomplished through psychotherapy or environmental interventions, are expected to have the highest impact to specifically reorganize the complexity of the human mind and thus achieve a solid and long-lasting improvement in mental health. Graphical Abstract: ga1 Highlights: Behavior is the interface between the central nervous system and the living environment. As interface, behavior is a unique starting point to address the complexity of the brain. As interface, behavior is a privileged level of control of brain structure and activity. Therapies directly targeting behavior are highly effective in treating mental illness.